Function of Brassica napus BnABI3 in Arabidopsis gs1, an Allele of AtABI3, in Seed Development and Stress Response - Xu, Peipei; Cai, Weiming (Frontiers in Plant Science, 2019)
Abscisic acid (ABA) has been implicated in plant adaptation to various environmental stresses in addition to the regulation of seed dormancy and leaf senescence. ABI3 is a B3 domain-containing family protein and functions in the ABA signalling pathway during seed development. To date, the ABI3 orthologous have not been studied in Brassica napus. The aim of this study is to investigate the function of BnABI3 in plant development and stress response. Here, we identified an Arabidopsis line (gs1) from a population of mutagenised seeds and showed that GS1 is a new allele of AtABI3. When the Arabidopsis gs1 mutant was transformed with the BnABI3 gene, the transformed plants produced seeds that turned yellow and acquired desiccation tolerance. Moreover, BnABI3 regulates seed coat development and mucilage secretion by directly targeting the AtMUM1 and AtGATL5 genes. In addition, we showed that BnABI3 expression rescued gs1 freezing-induced green seed colouration by targeting AtSGR1/2 in transgenic Arabidopsis. BnABI3 is also involved in lateral root development and conferred a novel interaction between ABA and auxin signalling in roots. The potential role of ABI3 protein in endoplasmic reticulum homoeostasis was also tested. Altogether, our results indicated that BnABI3 mediates both plant development and the stress response.